2016
DOI: 10.1080/1354750x.2016.1252966
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circulating protein biomarkers in patients with hepatocellular carcinoma concomitantly infected with chronic hepatitis C virus

Abstract: In HCC patients with chronic HCV infection, we identified a group of differentially expressed circulating proteins involved in regulating different cellular mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Biomarkers with gender disparity for HCC and oncogene expression have not been well established. SAA2 and ORM2 had been reported to be significantly up-regulated in HCC patients and been suggested as potential biomarkers [45][46][47]. For SERPINA1, the polymorphisms, fucosylation, and up-regulation of its isoforms have been suggested to be related to hepatocarcinogenesis, metastasis, and sorafenib-resistant [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers with gender disparity for HCC and oncogene expression have not been well established. SAA2 and ORM2 had been reported to be significantly up-regulated in HCC patients and been suggested as potential biomarkers [45][46][47]. For SERPINA1, the polymorphisms, fucosylation, and up-regulation of its isoforms have been suggested to be related to hepatocarcinogenesis, metastasis, and sorafenib-resistant [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…It participates in blood coagulation, inflammatory response, apoptosis regulation and the prevention process of metastasis in cancer cells (38,39). KNG1 is overexpressed in CRC and HCC (40) and is regarded as a potential prognostic marker for CRC, as patients with increased KNG1 expression exhibit decreased survival rates when compared with lower KNG1 expression patients (39,41). Additional studies reported that KNG1 may be involved in cholesterol and lipoprotein metabolism disturbance and take part in the complex interplay between the hemostatic system and immune response in hepatitis C virus (HCV)-associated HCC (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…KNG1 is overexpressed in CRC and HCC (40) and is regarded as a potential prognostic marker for CRC, as patients with increased KNG1 expression exhibit decreased survival rates when compared with lower KNG1 expression patients (39,41). Additional studies reported that KNG1 may be involved in cholesterol and lipoprotein metabolism disturbance and take part in the complex interplay between the hemostatic system and immune response in hepatitis C virus (HCV)-associated HCC (39,40). Differences in KNG1 expression were observed among patients with multidrug-resistant and drug-sensitive tuberculosis and healthy control patients, and it is suspected that blood coagulation serves a role in the resistant ability of KNG1 (42).…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive methods, including blood tests, are still very important. Published research has shown that PON1 is an enzyme that is mainly synthesized in the liver and released into the circulatory system [ 45 , 46 ]. The expression of PON1 is mainly affected by liver cells, and the use of PON1 in a predictive model may reduce other possible interference factors.…”
Section: Discussionmentioning
confidence: 99%